Pengaruh Literasi Keuangan dan Financial Self Efficacy Terhadap Financial Behavior Pada Generasi Z Lingkungan Kampus UIN Sumatera Utara - Raudhah Jannatun; Hendra Harmain; Wahyu Syarvina (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to identify and analyze directly or indirectly the influence of financial literacy and financial self-efficacy on the financial behavior of Generation Z in the UIN North Sumatra campus environment. The approach used in this research is a causal approach. The subjects of this study were students of the Sharia Accounting course at the UIN North Sumatra campus. In this study, a questionnaire was used as a data collection technique. Data analysis techniques in this study used a quantitative approach using statistical analysis using validity tests, reliability tests, classical assumption tests, hypothesis testing, and multiple linear analysis. In this study, the SPSS 22 program was used for data processing. The results showed that financial literacy had a positive and significant effect on financial behavior, financial self-efficacy had a negative and insignificant effect on financial behavior, and financial literacy and financial self-efficacy had a positive and significant effect on financial behavior.